Progressive matrix cracking master curves of mid and outer off-axis plies in CFRP laminates. (15th March 2018) - Pakdel, Hamed; Mohammadi, Bijan
Abstract: An energy based criteria is developed to predict the propagation of mid and outer-ply matrix cracks in laminates of type 0 n / θ m s and θ m / 0 n s with θ = 90, 75, 60 subject to uniaxial tensile loading. Numerous specimens with 14 different layups are tested and optical microscopy is implemented to detect matrix cracks during tensile tests. Matrix cracking master curve is plotted for over 300 data points obtained from experimental observation of all tested layups. A single critical energy release rate G mc is derived for off-axis and transverse ply cracking in contrast to previous studies which only included transverse plies. Crack densities of all tested layups are analytically predicted and compared to experimentally obtained crack densities. For the first time in the literature, critical energy release rate is confirmed to be a material property independent of laminate layup as far as analytical predictions of matrix crack densities are in accordance with experimental observations.